(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The problems of reasoning of placing the petrol stations with the help of the concept of public utility by means of geo-marketing analysis are studied in the article. The theoretical basis of defining and interpretation of territory marketing is formulated. The geo-marketing aspect of applying the concept of public utility in placing the petrol stations is revealed.